2024
DOI: 10.3390/agronomy14010141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Enzyme Activities and Soil Physicochemical Properties of Four Typical Halophytic Communities in Saline-Sodic Soil

Jie Zhou,
Yue Miao,
Liangliang Guo
et al.

Abstract: Four typical halophytic communities found in saline-sodic soil, including Phragmites australis, Suaeda glauca, Leymus chinensis, and Puccinellia parl, were investigated in this study. A comparison was made among the electrical conductivity (EC) value, pH value, soil organic carbon (SOC), and soil enzyme activity across various soil depths. The findings of this study indicate that the EC and pH levels of the soil at the 0–40 cm depth vary among the four communities, with Suaeda glauca having the highest values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that drought and salinity reduce the decomposition rate by inhibiting soil enzyme activity and microbial metabolism. Easily decomposed litter is more effective in improving soil fertility and productivity, while longer-lasting litter helps C fixation [26,27]. The conversion of litter to soil C components is more efficient [28].…”
Section: Effect Of Habitat Variability On the Characteristics And Rel...mentioning
confidence: 99%
“…Numerous studies have shown that drought and salinity reduce the decomposition rate by inhibiting soil enzyme activity and microbial metabolism. Easily decomposed litter is more effective in improving soil fertility and productivity, while longer-lasting litter helps C fixation [26,27]. The conversion of litter to soil C components is more efficient [28].…”
Section: Effect Of Habitat Variability On the Characteristics And Rel...mentioning
confidence: 99%